Children and Augmentative or Alternative Communication System (AACs). A perceptive vision of the role played by families and professionals. - García, M. Pilar; Madrid, Dolores; Galante, Rafael (Anales de Psicología / Annals of Psychology, 2017)
<span style="font-family: ’Garamond’,serif; font-size: 8pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: ES-TRAD; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;" lang="ES-TRAD">The present study accounts for the experience conducted with eight children, their families and the professionals in charge of the Early Intervention Program (EI) working with them during the whole process of learning, training and generalizing of an Augmentative or Alternative Communication System (AACs) used to try and <span style="font-family: ’Garamond’,serif; font-size: 8pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-SG; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;" lang="EN-SG">find<span style="font-family: ’Garamond’,serif; font-size: 8pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: ES-TRAD; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;" lang="ES-TRAD"> resources that will improve the quality of life of these participants. A qualitative paradigm has been applied and the data collection has been performed using focal groups during five one-hour-and-a-halves to two-hour sessions. Results obtained show the emotions and feelings arising within the family circles when other communication problems between the different environments where these children interact are added up to the functional diversity; professional experts in many contexts need to provide resources to respond to these necessities and requests originated by these children and their families. The resulting data underline the importance of the intervention used to enhance the attribution of competencies that capacitates families and neutralizes the attributions generating stress situations to finally find the most autonomous solutions to these issues. Reflections provided by professionals show the importance of knowing better the necessities of these children and their families for them to provide an efficient collaboration during the resource-finding process.